Factors influencing cooking method, frequency, and duration of meal preparation in Moroccan households - Imane Barakat; Mohammed Elayachi; Rekia Belahsen (National Institute of Public Health - National Institute of Hygiene, 2023)
Background. The construction of the consumer's identity is dependent on how they prepare their meals. Objective. Study the cooking methods, frequency, and duration of meal preparation in Moroccan households as well as the associated factors. Materials and methods. This work is a part of a study with a validated conceptual and methodological framework that was conducted in 507 households in the region of Rabat-Salé-Kenitra in Morocco. The characteristics of the population and data on the cooking methods, frequency, and duration of meal preparation were collected by a survey. Associations between variables were studied by univariate logistic regression with a significance level of p<0.05. Results. The majority of the population was aged between 35 and 65 years (76%) and lived in urban areas (70%). The univariate analysis showed that the urban area was a factor that hindered stewing (p=0.009), while the work status (p=0.04) and the marital status "Married" (p=0.04) were favorable factors; the household size (p=0.02) is a factor favoring steaming method; urban area (p=0.04), work status (p 0.03), nuclear family type (p<0.001), and household size (p=0.02) are factors hindering the use of oven cooking; urban area (p=0.02) and higher education level (p=0.04) are factors favoring the use of fried food, age category [20-34] years (p=0.04), higher education level (p=0.01) and work status (p=0.01) were factors that favored the use of grilling; nuclear family type, (p=0.04) and household size (p=0.03) were factors that hindered the preparation of breakfast; urban area (p=0.03) and Arab ethnicity (p=0.04) are factors hindering snack preparation; urban area (p<0.001) is a factor favoring dinner preparation; household size (p=0.01) and use of stewing at least four times a week (p=0.002) are factors hindering meal preparation time, while use of baking (p=0.01) is a favoring factor. Conclusion. The study results point towards the implementation of a nutritional education strategy based on combining habits, preferences, and good cooking practices.